MANAGEMENT OF ‘KATIGAT VATA’ W.S.R. TO LUMBAR SPONDYLOLISTHESIS - Dwivedi, *Amarprakash Prasidhnarayan; Anaya, Pathrikar (AYUSHDHARA, 2017)
Introduction: Lumbar Spondylolisthesis is a degenerative disorder of vertebral column, and describes the anterior displacement of a vertebra or the vertebral column in relation to the vertebrae below. It occurs most often in the lumbar spine and produces symptoms such as Low back pain, Painful Lumbar movement, Stiffness in lumbar region, Tingling numbness and weakness in Lower limb. This condition can be correlated with Katigat Vata. Methodology: The purpose of the study was to observe the efficacy of ‘Panchtikta Ghrit Guggulu’- internally adjuvant to Kati Basti with Til Oil, in the management of Katigat Vata w.s.r. to Lumbar Spondylolisthesis. The subjective assessment of dependent variables such as Pain, Lumbar movement, Stiffness, Tingling numbness and weakness in Lower extremities was done & appropriate statistical test was applied to find out the significance of treatment. Result: The result showed 79.23% patients got complete relief from Low back pain, 88.55 % patients got relief from Painful Lumbar movement and 93.02% patients relieved from Lumbar stiffness. Further, Tingling numbness present was relieved in 62.87% patients. Similarly, the patients having weakness in Lower limb were relieved to 58%. Conclusion: In this study, Panchtikta Ghrit Guggulu- internally and Til Oil Kati Basti (Locally), revealed practically workable, effective and complication free treatment, proved statistically significant and efficacious in the management of Katigat Vata.